IDENTIFIKASI TINGKAT KEPUASAN PASIEN JKN TERHADAP WAKTU TUNGGU PENDAFTARAN RAWAT JALAN DI RSUP DR. SARDJITO - Desi Syahbaniar (Jurnal Manajemen Informasi dan Administrasi Kesehatan, 2022)
The waiting time for JKN patients at Dr Sardjito Hospital is more than 60 minutes. This is not in accordance with the standards set by the Ministry of Health. The length of patient waiting time can lead to patient dissatisfaction. Hospital patient satisfaction with the services provided is determined by the difference between expectations and perceived services (reality). The purpose of this study was to identify the level of satisfaction of JKN patients with waiting times for outpatient registration at RSUP Dr. Sardjito Yogyakarta. This study is a quantitative study with 97 outpatient JKN patients as respondents. Data was collected using a questionnaire with the help of interviews. The method used is service quality (servqual). 5 dimensions of service quality include tangibles, reliability, responsiveness, assurance and empathy. The results showed that the frequency distribution of the satisfaction level of JKN patients at the "unsatisfied" point was 76 respondents (78.35%), the frequency distribution of satisfaction with waiting time for outpatient registration of JKN patients in the "unsatisfied" category was the highest in the tangible dimension. that is as many as 66 respondents (68.04%).Keyword: Satisfaction Level, Waiting Time For Registration, JKN Patient